1995
DOI: 10.1093/hmg/4.11.2025
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence of the coding region of the ATM gene reveals similarity to cell cycle regulators in different species

Abstract: Ataxia-telangiectasia (A-T) is an autosomal recessive disorder involving cerebellar degeneration, immunodeficiency radiation sensitivity, and cancer predisposition. A-T heterozygotes are moderately cancer prone. The A-T gene, designated ATM, was recently identified in our laboratory by positional cloning, and a partial cDNA clone was found to encode a polypeptide with a PI-3 kinase domain. We report here the molecular cloning of a cDNA contig spanning the complete open reading frame of the ATM gene. The predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
270
0
7

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(283 citation statements)
references
References 0 publications
6
270
0
7
Order By: Relevance
“…This is consistent with the result described previously that only p53 mutated (EJ and TCC-sup) but not p53 wild-type (Lavin and Shiloh, 1997). Mutated ATM genes in yeast, Drosophila and mammals also result in a variety of phenotypes with features similar to human AT cells (Savitsky et al, 1995). ATM deficiency leads to growth retardation, infertility and cancer-predisposition in mice (Barlow et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the result described previously that only p53 mutated (EJ and TCC-sup) but not p53 wild-type (Lavin and Shiloh, 1997). Mutated ATM genes in yeast, Drosophila and mammals also result in a variety of phenotypes with features similar to human AT cells (Savitsky et al, 1995). ATM deficiency leads to growth retardation, infertility and cancer-predisposition in mice (Barlow et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…In mice expressing this mutant Nbs1, there was a defect in DNA damage-induced intra-S checkpoint activation in mouse (Bakkenist and Kastan, 2003;Kozlov et al, 2006). The identified domains within ATM consist of the nuclear localization signal (NLS) , the leucine zipper (LZ) (Savitsky et al, 1995b), the FRAP/ATM/TRRAP (FAT) domain (Bosotti et al, 2000), the Kinase domain (PI3-K) (Savitsky et al, 1995a), and the FAT c-terminal (FATC) domain (Bosotti et al, 2000). (b) Nbs1 is a 90 kDa protein, consisting of 754 amino acids.…”
Section: Role Of the C-terminus Of Nbs1mentioning
confidence: 99%
“…The ATM protein is a member of an expanding family of large proteins sharing the PI 3-kinase-like domain which were identi®ed in yeast, Drosophila and mammals. These proteins are involved in maintaining genome stability and cell cycle control, and in cellular responses to damaging agents (Savitsky et al, 1995b;Zakian, 1995;Jackson, 1995;Lavin and Shiloh, 1997). Two members of this family, DNA-dependent protein kinase (Hartley et al, 1995) and FRAP (Brown et al, 1995), were shown to be protein kinases, and it is likely that most or all of these proteins share this activity (Hunter, 1995).…”
Section: Introductionmentioning
confidence: 99%